Inovasi Kegiatan Melipat Untuk Meningkatkan Perkembangan Fisik Motorik Anak Usia Dini - Muhammad Sajudin (https://journal.metanusantara.com/impact/index.php/jpk, 2025)
Early childhood physical motor development is an important aspect in their readiness for further education. However, many children in rural areas experience barriers in fine motor development due to the lack of practice-based learning methods. This study aims to evaluate the effectiveness of folding activities as a strategy to improve early childhood fine motor skills in Nglebur Village, Jiken Sub-district, Blora Regency. This research uses the method of Participatory Action Research (PAR) involving PAUD and TK children as the main informants, as well as teachers and parents as supporting data sources. Data were collected through participatory observation, in-depth interviews, and analysis of children's work before and after the intervention. The results showed that the systematic implementation of folding activities was able to significantly improve children's fine motor skills. Before the intervention, about 75% of the children experienced difficulties in hand-eye coordination, while after the programme was implemented for one month, the percentage decreased to 30%. In addition, the involvement of teachers and parents in this programme contributed to the successful implementation of practice-based learning methods.